An N‐of‐1 study of daily alcohol consumption following minimum unit pricing implementation in Scotland. (12th January 2021) - Kwasnicka, Dominika; Boroujerdi, Massoud; O'Gorman, Aileen; Anderson, Martin; Craig, Peter; Bowman, Louise; McCann, Mark
Abstract: Background and aims: Within the context of Scotland's policy change to implement a minimum unit price (MUP) per unit of alcohol sold in licensed premises, this study used an N‐of‐1 design to assess between‐person differences in the psychological and social factors associated with daily alcohol consumption. Design and setting: A mixed‐methods approach combined N‐of‐1 observational studies, comprising daily surveys followed by qualitative social network interviews (not reported here). Peer researchers with lived experience of substance use were involved in the study design and fieldwork was conducted in towns and rural areas in the East of Scotland. Participants/cases: Twenty‐five adults with current or recent history of alcohol dependence recruited for three 12‐week waves: 11 in wave 1 (pre‐MUP), 11 in wave 2 (pre‐ and post‐MUP) and three in wave 3 (post MUP). Measurements: Gender, age, alcohol and other drug use history. Daily surveys for 12 weeks captured information about factors in the last 24 hours, e.g. amount and type of alcohol consumed, stress, social contact. Findings: Each participant was in the daily survey for a mean of 64 days [standard deviation (SD) = 42; median = 59], with a response rate of 48%; 15 participants provided sufficient data for analysis. Factors related to daily alcohol consumption differed between individuals. Models suggested that some individuals with high initial consumption reduced drinking after MUP, but explanatory factors differed, e.g. changing motivation was important for some, while alcohol availability was important for others. Conclusions: Adapting N‐of‐1 methods for an observational study uncovered differences in alcohol consumption change before and after minimum unit pricing implementation in Scotland, evidence of individual differences in the factors relating to alcohol consumption patterns and some evidence that post‐MUP consumption changes may be related to changing psychosocial factors.